Access control via coalitional power game - Guruacharya, Sudarshan (2013)
This paper considers the problem of access control in the uplink transmission of an OFDMA femtocell network. An underlying noncooperative power game has been devised, based on which a coalition game is formulated by taking a suitable value function. Only two complementary coalitions are allowed to exist in order to reflect the set of transmitters connected to either the macro base station or the femto access point. The transmitters in the same coalition cooperate by operating on non-interfering subchannels, while those in the complementary coalition are assumed to operate so as to cause maximum jamming. The value of a coalition is obtained as the max-min of utility sum of each individual in the given coalition. In the process, we also examine the optimal jamming strategy of the complementary coalition. Finally, we argue that the obtained value function cannot be super-additive. Since the super-additivity property is required for some of the solutions of cooperative game theory, we resort to the Shapley value solution, for which the super-additivity need not hold, to allocate the payoff to each user in a given coalition. Assuming that the transmitters want to be in the coalition that maximizes their payoff, we form a Markov model to obtain the stable coalition structure. We take these stable coalition structures as the required solution of our access control problem.